Intelligence : from secrets to policy - Lowenthal, Mark M. (California and UK: CQ Press & SAGE, 2022)
"Mark M. Lowenthal's trusted guide is the go-to resource for understanding how the intelligence community's history, structure, procedures, and functions affect policy decisions. In the fully updated Ninth Edition of Intelligence, the author addresses cyber security and cyber intelligence throughout, expands the coverage of collection, comprehensively updates the chapters on nation-state issues and transnational issues, and looks at foreign intelligence services, both large and small"--
Includes bibliographical references and index.
Keywords: Intelligence service -- United States -- Planning; Intelligence service -- United States -- Forecasting